2019
DOI: 10.1016/j.jaad.2018.07.043
|View full text |Cite
|
Sign up to set email alerts
|

Dupilumab use in allergic contact dermatitis

Abstract: Funding sources: None.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
1
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(24 citation statements)
references
References 5 publications
0
22
1
1
Order By: Relevance
“…Within 8 weeks after the start of dupilumab therapy, his dermatitis drastically improved. Machler et al reported 15 cases of patients treated with dupilumab for recalcitrant dermatitis . Eleven patients had a history of childhood AD.…”
Section: Discussionmentioning
confidence: 99%
“…Within 8 weeks after the start of dupilumab therapy, his dermatitis drastically improved. Machler et al reported 15 cases of patients treated with dupilumab for recalcitrant dermatitis . Eleven patients had a history of childhood AD.…”
Section: Discussionmentioning
confidence: 99%
“…63,64 Interestingly, in 1 case report, dupilumab administration resulted in the onset of recall dermatitis at the patch test site for colophony 24 hours after administration, suggestive of nonetype 2 immune pathways contributing to underlying dermatitis. 65 62 64 adults with AD 17 with PTþACD 14 with SACD 33 without ACD Retrospective study 64 7 adults with localized dermatitis refractory to dupilumab were PT 6 adults underwent PT before dupilumab Retrospective study 66 15 adults with AD with hand dermatitis and/or childhood AD had PT performed Retrospective study 63 48 adults with AD underwent PT Case report 65 42-year-old female with colophony allergy Case report 67 A 54-year-old surgeon with hand dermatitis refractory to dupilumab had a PT Case report 68 A 44-year-old man with nickel allergy to metal endovascular stents on MMF and prednisone After treatment, patients with PTþACD and SACD had similar decreases in BSA, IGA, and pruritus compared with those without ACD. All 7 patients had at least 1 positive PT result, with at least >1 or stronger reaction.…”
Section: Managementmentioning
confidence: 99%
“…In addition, products marketed for children with AD may contain weakly T H 2-sensitizing allergens, such as fragrances and CAPB, which affect atopic skin more. 53,66 In patients with severe AD, who warrant treatment with dupilumab, patch testing can still be performed, and contact allergen avoidance combined with dupilumab may provide additional clinical benefit in the relief of underlying dermatitis. Patch testing with patient's personal products along with standardized series is recommended.…”
Section: Ustekinumabmentioning
confidence: 99%
“…Three of these studies showed mean improvements ranging from 85 to 90% in the percentage of body surface area affected by ACD; 17 of the 23 patients included in these studies had a history of AD. [18][19][20] The fourth study, a retrospective chart review, demonstrated improvement with dupilumab in 64 AD patients, 31 of whom had confirmed or suspected ACD. AD patients with and without ACD responded equally well to dupilumab.…”
mentioning
confidence: 99%